Hubungan Pengetahuan Ibu tentang Posyandu dengan Perilaku Kunjungan Posyandu Balita - Shin Chen Lara; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Jurnal Surya Medika (JSM), 2022)
Integrated service post is the earliest health service center for toddlers. However, in reality, the community members themselves still do not use Integrated service posts to monitor toddlers' growth with the excuse that he was busy, so he did not have time to bring his toddler to school: integrated service posts and lack of knowledge about the importance of monitoring growth flowers in toddlers. A person's level of expertise affects an lt individual behavior, where the higher the level of understanding of mothers about the benefits of Integrated service post, the higher the level of awareness to play a role. In the Integrated service post-program, low knowledge of Integrated service post will cause a low level of understanding of mothers who have toddlers to visit Integrated service post. This study was conducted to determine the relationship between mothers' knowledge about Integrated service posts with the behavior of toddlers' Integrated service post-visit. This research method is Literature Review. The study design used is a cross-sectional and correlation analytic survey. Using Google Scholar (2017-2020). Articles in Indonesia. Strategy using PICOS with Inclusion and Exclusion criteria. The result showed that as many as six pieces analyzed stated a relationship between a mother's knowledge about integrated service post and visiting behavior of a toddler Integrated service post. Mother knowledge is related to seeing the Integrated service post for toddlers. Good knowledge will lead to good behavior visiting the Integrated service post. Age and education are factors that affect understanding, affecting the behavior of visits to Integrated service post toddlers. Mature age makes it so easy to accept and disapprove of the information obtained, and with a good education, it is broad knowledge gained so that a person who knows, receives data and can apply it in their lives.